2020
DOI: 10.1101/2020.06.24.20121905
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The therapeutic effectiveness of Convalescent plasma therapy on treating COVID-19 patients residing in respiratory care units in Baghdad, Iraq

Abstract: Objectives: The current COVID-19 pandemic needs unconventional therapies to tackle the resulted high morbidity and mortality. Convalescent plasma is one of the therapeutic approaches that might be of benefit. Methods: Forty nine early-stage severe and critically-ill COVID-19 patients residing in RCU of three hospitals in Baghdad, Iraq were included, 21 received convalescent plasma while 28 did not receive, namely control group. Recovery or death, length of stay in hospital, and improvement in the clinical cour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
209
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(214 citation statements)
references
References 10 publications
4
209
1
Order By: Relevance
“…Another RCT [104] (49 participants, of whom 21 received convalescent plasma) showed that convalescent plasma reduced duration of infection about 4 days (19.3 ± 6.9 days vs.23.42 ± 6.4 days, P < 0.05), and showed less death rate (1/21 vs. 8/28, P < 0.05).…”
Section: Implementation Considerationsmentioning
confidence: 99%
“…Another RCT [104] (49 participants, of whom 21 received convalescent plasma) showed that convalescent plasma reduced duration of infection about 4 days (19.3 ± 6.9 days vs.23.42 ± 6.4 days, P < 0.05), and showed less death rate (1/21 vs. 8/28, P < 0.05).…”
Section: Implementation Considerationsmentioning
confidence: 99%
“…Convalescent plasma is a century-old passive antibody therapy that has been used to treat outbreaks of novel infectious diseases, including those affecting the respiratory system 1,2 . Due to the lack of vaccines or monoclonal antibody therapies, human convalescent plasma is currently being used wordwide to treat coronavirus disease 2019 (COVID- 19), which is caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) [2][3][4][5] . However, evidence for therapeutic COVID-19 convalescent plasma efficacy still requires definitive support from large randomized clinical trials (RCT).…”
Section: Brief Communicationmentioning
confidence: 99%
“…25 Wisconsin, USA 27 Forest plot illustrating odds ratios (OR) and 95% confidence intervals for controlled studies and aggregate fixed effect models. Fixed effect ORs for Duan et al 26 , Rasheed et al 19 , Perotti et al 23 , Hegerova et al 21 , Zeng et al 9 , Donato et al 10 , Liu et al 22 , Salazar et al 11 , Gharbharan et al 8 , Xia et al 12 , Abolghasemi et al 24 , and Li et al 7 are represented in blue. The aggregate fixed effect model OR is represented in shaded blue.…”
Section: Brief Communicationmentioning
confidence: 99%
“…Clinical studies with CCP suggest that higher titers of neutralizing antibody provide superior clinical benefit to recipients. [9,10] These findings support the value of anti-viral antibodies in eradicating viral infection in patients, lessening disease severity, and potentially reducing transmission.…”
Section: Introductionmentioning
confidence: 70%